The Influence of Activation Processes on Ion Sputtering - Pranevicius, L. L.; Milcius, D.; Pranevicius, L. (Elektronika ir Elektrotechnika, 1997)
The role of activated surface atoms on the kinetics of heterogeneous processes in plasma is considered. The kinetics of the surface composition is studied including processes of preferential sputtering, thermal activated desorption and generation of activated atoms. The emphasis is made on the generation of multi-activated atoms. The mathematical formalism enabling to include these processes into the general scheme of ion beam induced processes is presented.